Carl Hugo Gutsche, 1843-1926 : the significance of his life and ministry for the Baptist churches and missions in Southern Africa - Haus, Fritz Hugo (Stellenbosch : Stellenbosch University, 2012)
Thesis (DTh)--Stellenbosch University, 1999.